An immunohistochemical study of the lining epithelium of odontogenic keratocyst. - Siar, C.H.; Ng, K.H. (1995)
The lining epithelium of 15 cases of odontogenic keratocyst (OKC) was evaluated immunohistochemically. The peroxidase-antiperoxidase technique was applied to study the distribution of polyclonal keratin and S-100 protein while the indirect method was used to examine monoclonal vimentin and desmin reactivity. Consistent positive keratin staining was revealed in the lining epithelium of all 15 OKCs with additional intense staining in the stratum corneum. None of the cases showed vimentin or desmin reactivity within the lining epithelium elements. One of the 15 cysts studied showed positive S-100 protein staining in the nuclei of the lining epithelial cells. The pertinent literature on the immunophenotyping of the lining epithelium of OKC is reviewed.